2017
DOI: 10.1002/slct.201702020
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Bioresource‐Derived Components for Molecular Keypad Lock and IMPLICATION Logic Gate Construction

Abstract: A In view of security information storage, preserving the information at the molecular level is an attractive research goal. This eventually led to the extensive development of “Molecular Keypad Locks” which can be opened only by a particular sequence of chemical inputs. Here we report a molecular keypad lock from two bioresource derived components, one is an azobenzene system from cardanol and a graphene quantum dot derived from honey. This system further used to construct an IMPLICATION logic gate and a fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Figure 8a describes the isomerization of an azobenzene group functionalized on GQDs via hydrogen bonding [96]. Figure 8b describes the isomerization of an azobenzene group functionalized on GO via covalent bonding [97].…”
Section: Photoisomerization Of Gd-azo Compositesmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 8a describes the isomerization of an azobenzene group functionalized on GQDs via hydrogen bonding [96]. Figure 8b describes the isomerization of an azobenzene group functionalized on GO via covalent bonding [97].…”
Section: Photoisomerization Of Gd-azo Compositesmentioning
confidence: 99%
“…The synthesis strategies for GO-AZO and GQDs-AZO composites are similar because they both have oxygen based functional groups on their surfaces. Renuka et al reported the formation of GQD-AZO composites through hydrogen bonding [96]. Both RGO-AZO hybrids showed an enhanced current value upon UV illumination due to the trans ⇌ cis isomerization of the azobenzene system.…”
Section: Hydrogen Bondingmentioning
confidence: 99%
See 2 more Smart Citations
“…For some technical reasons this gate was ignored in digital electronics for many years, but recently interest to this gate has been returned based on its straightforward realization in memristive switches . The IMPLY logic gate has been realized in many chemical systems, including biomolecular systems based on DNA molecules, particularly operated as cell biology processes . However, the IMPLY gate was rarely demonstrated with enzyme‐catalyzed reactions …”
Section: Figurementioning
confidence: 99%